Correlation between Mitral Valve Area and Right Ventricle Function based on TAPSE (Tricuspid Annular Plane Systolic Excursion) Parameter in Mitral Stenosis Patient - Hashina Zulfa; Erika Maharani; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2018)
Background: Mitral stenosis is the most common mitral valve disease found in Indonesia. Mechanical obstruction of blood flow from left atrium to left ventricle is compensated by pressure elevation in the left atrium and pulmonary circulation. It leads to right ventricle dysfunction which can be scored using TAPSE (Tricuspid Annular Plane Systolic Excursion) Parameter.Aim: The goal of this study is to assess the relationship between mitral valve area and right ventricle function based on TAPSE parameter in mitral stenosis patient.Methods: This study was conducted in Dr. Sardjito Hospital from May until July 2017. This was a part of mitral stenosis registry study. The parameter used was planimetry mitral valve area and TAPSE from echocardiography. The relationship between mitral valve area and TAPSE score we reanalyzed using Spearman correlation test in SPSS software.Results: The total sample included in this study was 132 people, consisted of thirty-eight (28.79%) males and ninety-four (71.21%) females. The range of the subjects’age was 18 68 year oldand the mean was 43.31±11.13 year old. The body mass index median was 21.24 (14.24–35.38) kg/m2. The subjects were dominated by severe degree mitral stenosis patients, those were ninety-three (70.45%) people, followed by moderate degree patients, those were thirty-two (24.24%) people, and mild degree patients, those were seven (5.30%) people. Twenty-eight (21.21%) people had isolated mitral stenosis. The mitral valve area median was 0.8 (0.27–1.90) cm2. The TAPSE score range was 6–30 mm and the mean was 17.48±4.58 mm. The result from Spearman correlation test showed that the relationship strength between mitral valve area and TAPSE score were very weak (r=0.167) with significant p-value (p=0.028).Conclusion: There is a statistically significant positive relationship with very weak strength between mitral valve area and TAPSE score as a right ventricle function parameter in mitral stenosis patients (r = 0.167, p = 0.028).